Preschool appropriate practices environment, curriculum, and development - Beaty, Janice J. (Wadsworth Cengage Learning, 2014)
This book uses the creative approach--letting the learning environment do the teaching--and speaks to college students as well as teachers in the field with practical applications based on current research. Each chapter is based on one of the learning centers in a preschool classroom, allowing readers to learn how to set up these centers in a self-directed environment. This approach encourages children ages 3 to 5 to become deeply involved in their own learning. A second important theme, let the teacher be a facilitator of learning, assists readers in their understanding of: (1) how to observe children's developmental levels, (2) what developmentally appropriate activities to provide, (3) how to serve as a behavior model in these centers, and (4) how best to support children in their learning. Readers learn how to determine children's developmental levels of manipulation, mastery, and meaning by observing their interactions with materials and one another. These activities integrate with the National Association for the Education of Young Children's (NAEYC) developmentally appropriate practice (DAP), a nationally recommended set of early childhood practices.